[CINE-MRT for the study of the effects of regional left ventricular wall motion disorders on global heart function after a myocardial infarct and revascularization] - Sandstede, J; Lipke, C; Beer, M; Harre, K; Pabst, T; Kenn, W; Neubauer, S; Hahn, D (1999)
PURPOSE: To determine changes in global cardiac function and mass caused by infarct-associated regional wall motion abnormalities and to compare the changes after revascularization in patients with and without improvement of regional contractility. MATERIALS AND METHODS: 21 patients with regional left ventricular wall motion abnormalities and associated coronary artery stenoses requiring revascularization were examined with a Cine FLASH-2D sequence 26 +/- 12 days after their first myocardial infarction and re-examined three months after revascularization. Regional contractility and volumes and masses of both ventricles were determined. RESULTS: After revascularization, regional wall motion improvement led to decreased left ventricular volumes and improved ejection fractions, whereas patients with persisting wall motion defects showed unchanged left ventricular functional parameters. Comparing both groups of patients, the patients with improvement of regional contractility revealed lower end-systolic volumes and higher ejection fractions at follow-up. Cardiac masses and right ventricular parameters were not different, patients with a depressed right ventricular ejection fraction showed improvement at follow-up. DISCUSSION: After myocardial infarction, revascularization of the infarct-related coronary artery leads to an improvement of left ventricular function only if there is also an improvement of regional contractility. An effect on right ventricular function was not observed three months after the first small- or middle-sized myocardial infarction.